Deformation behaviour and microstructure characteristics of aluminium alloy cylindrical toothed parts by an innovative crossed-axes helical rolling process - Kun Li; Chao Zhang; Ming Chang; Shengdun Zhao (Journal of Materials Research and Technology)
Tooth rolling process is an advanced manufacturing technology for high-performance toothed parts, with broad application prospects in the field of lightweight components. This paper conducts in-depth research on the manufacturing of toothed parts with 6061 aluminium alloy on the basis of the proposed novel crossed-axes helical rolling process. The deformation characteristics during the rolling process were analysed and the formed parts with a complete and full tooth profile were obtained by an experiment. The microhardness in tooth bottom and flank regions improved greatly, and the maximum hardness increased by 133.3%. The hardness on the front flank of the tooth profile was obviously greater than on the blank flank. The microstructure characteristics in different strain accumulation regions of the formed tooth were analysed in detail and the correlation between strain accumulation, hardness distribution and microstructure was discussed. Results show that mass refined grains were observed in the microstructure from the tooth bottom and flank regions, and the average grain size significantly decreased from 7.6 μm of the original blank to 1.5 and 1.2 μm, respectively. The initial textures of the extruded 6061 aluminium alloy were weaken in the formed tooth bottom and flank regions. Substructures formed within some grains in the centre of the formed tooth, resulting in a slight increase in hardness. The significantly increased hardness in the tooth bottom and flank regions is due to some substructures being further transformed into new fine grains as a result of intense strain accumulation.